Energy efficient residential buildings assessment using building information modeling - Amin Fakhkhar Zadeh, 1985-; Khairulzan Yahya, supervisor; Fakulti Kejuruteraan Awam (2013)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2013